Anti-vascular endothelial growth factor monotherapy or combined with verteporfin photodynamic therapy for retinal angiomatous proliferation: a systematic review with meta-analysis - Fallico, Matteo; Macchi, Iacopo; Maugeri, Andrea; Favara, Giuliana; Barchitta, Martina; Magnano San Lio, Roberta; Agodi, Antonella; Russo, Andrea; Longo, Antonio; Avitabile, Teresio; Castellino, Niccolò; Reibaldi, Michele; et al. (Frontiers in Pharmacology, 2023)
Purpose: To assess functional and anatomical outcomes of intravitreal anti-Vascular Endothelial Growth Factor (anti-VEGF) monotherapy versus combined with verteporfin Photodynamic Therapy (PDT) for Retinal Angiomatous Proliferation (RAP). Methods: Studies reporting outcomes of intravitreal anti-VEGF monotherapy and/or in combination with verteporfin PDT in RAP eyes with a follow-up ≥ 12 months were searched. The primary outcome was the mean change in best corrected visual acuity (BCVA) at 12 months. Mean change in central macular thickness (CMT) and mean number of injections were considered as secondary outcomes. The mean difference (MD) between pre- and post-treatment values was calculated along with 95% Confidence Interval (95%CI). Meta-regressions were performed to assess the influence of anti-VEGF number of injections on BCVA and CMT outcomes. Results: Thirty-four studies were included. A mean gain of 5.16 letters (95% CI= 3.30-7.01) and 10.38 letters (95% CI= 8.02-12.75) was shown in the anti-VEGF group and combined group, respectively (anti-VEGF group vs combined group, p< 0.01). A mean CMT reduction of 132.45 µm (95% CI= from -154.99 to -109.90) and 213.93 µm (95% CI= from -280.04 to -147.83) was shown in the anti-VEGF group and combined group, respectively (anti-VEGF group vs combined group, p< 0.02). A mean of 4.9 injections (95%CI=4.2-5.6) and 2.8 injections (95%CI=1.3-4.4) were administered over a 12-month period in the anti-VEGF group and combined group, respectively. Meta-regression analyses showed no influence of injection number on visual and CMT outcomes. High heterogeneity was found across studies for both functional and anatomical outcomes. Conclusions: A combined approach with anti-VEGF and PDT could provide better functional and anatomical outcomes in RAP eyes compared with anti-VEGF monotherapy.